2005
DOI: 10.1016/j.cardiores.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 in cardiomyocyte mitochondria and its increase by ischemic preconditioning

Abstract: These data demonstrate that Cx43 is localized at cardiomyocyte mitochondria and that IP enhances such mitochondrial localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
234
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(256 citation statements)
references
References 36 publications
17
234
0
5
Order By: Relevance
“…Moreover, SB216763 had only a minimal effect on mitoK ATP channel activity of mitoplasts from conditional Cx43-deficient mice [4-hydroxytamoxifen (4-OHT)-treated Cx43 Cre-ER(T)/fl mice] ( Fig. 1 B and F and Table 1), which contain a residual 5-10% cardiac Cx43 (11), supporting the notion that GSK3 transfers protective signaling via Cx43 onto mitoK ATP channels.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, SB216763 had only a minimal effect on mitoK ATP channel activity of mitoplasts from conditional Cx43-deficient mice [4-hydroxytamoxifen (4-OHT)-treated Cx43 Cre-ER(T)/fl mice] ( Fig. 1 B and F and Table 1), which contain a residual 5-10% cardiac Cx43 (11), supporting the notion that GSK3 transfers protective signaling via Cx43 onto mitoK ATP channels.…”
Section: Resultsmentioning
confidence: 55%
“…More complete ablation of Cx43 (residual 5-10% Cx43) was induced in adult Cx43 Cre-ER(T)/fl mice by i.p. injection of 3 mg of 4-OHT once per day on 5 d consecutively as previously described (11). These animals were killed at day 12 after the first injection.…”
Section: Methodsmentioning
confidence: 99%
“…The production of ROS is one of the byproducts of mitochondrial respiration, and mitochondrias have frequently been considered as the main source of cellular- derived ROS (25). Mitochondrial Cx43 has been shown to play a role in mediating the cardioprotective effect of ischemic preconditioning through modification of the mitochondrial content and membrane potential (26). Analysis of O 2 − generated by mitochondrial activity showed that, similarly to overall intracellular ROS levels, mitochondrial-derived superoxide levels were increased in 5-FU-treated H-Cx43-deficient HSCs compared with WT HSCs (Fig.…”
Section: To Clarify Whethermentioning
confidence: 99%
“…In cardiomyocytes, Cx43 can also localize within mitochondrial membranes, where it has been implicated in enhanced ischemic preconditioning response. Accordingly, some authors reported that during stress conditions, as occurs in myocardial ischemia, the levels of mitochondrial Cx43 raise, which could contribute to keep the mitochondrial permeability transition pore (MPTP) in a closed state, delaying the release of apoptotic proteins and cytochrome c, thus reducing ischemia/reperfusion (I/R) injury (7,8).…”
mentioning
confidence: 99%